Neonatal mortality among neonates admitted to NICU of Hiwot Fana specialized university hospital, eastern Ethiopia, 2020: a cross-sectional study design - Addis Eyeberu; Hirpo Shore; Tamirat Getachew; Genanaw Atnafe; Merga Dheresa (BMC, 2021)
Abstract Background In Ethiopia, neonatal mortality is unacceptably high. Despite many efforts made by the government and other partners to reduce neonatal mortality; it has been increasing since 2014. Factors associated with neonatal mortality were explained by different researchers indifferently. There is no clear evidence to identify the magnitude of neonatal mortality and associated factors in the study area. The study aimed to assess the magnitude and factors associated with neonatal mortality. Methods Facility-based cross-sectional study was conducted among 834 randomly selected neonates. The study was conducted from February 20 to March 21, 2020. Data were extracted from medical records using a checklist adapted from the World Health Organization, and neonatal registration book. The data were inserted into Epi-data version 3.1 and then exported into SPSS window version 20 for analysis. Bivariate and multivariate analyses were employed to identify the association between independent variables and the outcome variable. Results Magnitude of neonatal mortality was 14.4% (95% CI:11.9,16.7). Being neonates of mothers whose pregnancy was complicated with antepartum hemorrhage [AOR = 4.13, 95%CI: (1.92,8.85)], born from mothers with current pregnancy complicated with pregnancy-induced hypertension [AOR = 4.41, 95%CI: (1.97,9.86)], neonates of mothers with multiple pregnancy [AOR = 2.87, 95% CI (1.08,7.61)], neonates delivered at the health center [AOR = 5.05, 95%CI: (1.72,14.79)], low birth weight [AOR = 4.01, 95%CI (1.30,12.33)], having perinatal asphyxia [AOR =3.85, 95%CI: (1.83,8.10)], and having early-onset neonatal sepsis [AOR = 3.93, 95%CI: (1.84,8.41)] were factors significantly associated with neonatal mortality. Conclusion The proportion of neonatal mortality was relatively in line with other studies but still needs attention. Antepartum hemorrhage, Pregnancy-induced hypertension, place of delivery, low birth weight, having perinatal asphyxia, and having neonatal sepsis were independent factors. The hospital, and health care workers should give attention to neonates admitted to intensive care units by strengthening the quality of care given at neonatal intensive care unit like infection prevention and strengthening early detection and treatment of health problems during Antenatal care visit.